Reflection of the Oligopolistic Market Structure in the Construction of a Financial Model - Radkov, Bozhidar (Research Papers, 2024)
The specific methodology for determining indicator weights is one of the key components in the construction of any financial model. Given the specificities of the oligopolistic market structure, it is necessary to reflect its existence in the construction of financial models that have the task of establishing the financial performance of oligopolistic companies. It is possible to take into account the presence of the oligopolistic market structure by the choice a methodology for determining the weights of indicators in a specific financial model. In this research paper, a specific mathematical model that takes into account the presence of the oligopolistic market structure is presented.
Keywords: Oligopolistic market structure; Market share; Market concentration ratio (cr); Herfindahl-hirschman index (hhi); Weight of financial indicators